Traumatic Arthrotomy with Pneumarthrosis on Plain Radiograph of the Knee - Timothy D. Roberts, MBChB (Western Journal of Emergency Medicine, 2016)
An eight-year-old boy presented to the emergency department (ED) with a 2cm-long laceration over the prepatellar region of his left knee after falling over and cutting his knee on broken glass. Physical examination demonstrated the laceration breached the dermis but otherwise there was no obvious defect in the deep fascial layer. He had a free range of motion of his knee and clinically his extensor mechanism was intact; however, a plain lateral radiograph showed that he had pneumarthrosis of his knee joint. Within six hours of injury the wound was formally explored in the operating room and a small breach in the knee capsule was found. The wound edges were debrided, the knee joint irrigated and the skin closed primarily. Following surgery he received 24 hours of antibiotic coverage with a first-generation cephalosporin.